Phylogeny of Artiodactyla and Cetacea - based on mitochondrial genomes - Ursing, Björn M (Department of Genetics, Lund University, 1998)
Artiodactyla (eved-toed ungulates) and Cetacea (whales) are two mammalian orders that are commonly recognised as sistergroups. Recently it has been suggested that Cetacea originated within Artiodactyla, but the relationships among the different artiodactyl lineages and Cetacea have not been conclusively established. In the present study the mitochondrial genome of the pig (Sus scrofa), the hippopotamus (Hippopotamus amphibius), the alpaca (Lama pacos) and the sperm whale (Physeter macrocephalus) have been analysed. These sequences have been used in phylogenetic analyses together with those of two baleen whales, two ruminants and several other eutherian mammals. The study is based on the concatenated nucleotide and amino acid sequences (10,554 and 3,518 characters respectively) of all the mitochondrial protein coding genes except NADH6. Analyses on both data sets identified a basal divergence of the recent artiodactyls into Ruminantia (bovids, deers, tragulids and giraffs), Tylopoda (camels and llamas) and Suina (pigs and peccaries). However, the order in which these lineages diverged was not conclusively resolved. A clade of Ruminatia, Hippopotamidae (hippopotamuses) and Cetacea was identified where the sistergroup relationship between Cetacea and Hippopotamidae was well supported, making both Artiodactyla and Suiformes (pigs, peccaries and hippopotamuses) paraphyletic. Molecular data in conjunction with the palaeontological record have suggested that the primary divergence between recent whales into Odontoceti (toothed whales) and Mysticeti (baleen whales) occured 32-34 million years before present (MYBP). This calibration point suggests that the primary split between Ruminantia, Tylopoda and Suina occured at =65 MYBP, the divergence between Ruminantia and Hippopotamidae/Cetacea at 60 MYBP and the divergence between Hippopotamidae and Cetacea at =55 MYBP.